Mesityl or Imide Acridinium Photocatalysts: Accessible Versus Inaccessible Charge‐Transfer States in Photoredox Catalysis. Issue 8 (7th June 2019) - Gini, Andrea; Rigotti, Thomas; Pérez‐Ruiz, Raúl; Uygur, Mustafa; Mas‐Ballesté, Rubén; Corral, Inés; Martínez‐Fernández, Lara; de la Peña O'Shea, Victor A.; García Mancheño, Olga; Alemán, José
Abstract: A study on C9‐imide acridinium photocatalysts with enhanced photoredox catalytic activity with respect to the well‐established C9‐mesityl acridinium salt is presented. The differences observed rely on the diverse accessibility of singlet charge‐transfer excited states, which have been proven by CASPT2/CASSCF calculations, fluorescence and quenching studies. Abstract : Stop and go : A study on C9‐imide acridinium photocatalysts with enhanced photoredox catalytic activity with respect to the well‐established C9‐mesityl acridinium salt is presented. The differences observed rely on the accessibility of singlet charge‐transfer excited states, as proven by CASPT2/CASSCF calculations, fluorescence and quenching studies.